Biocomplatible parylene neurocages. - Tooker, A.
This paper presents a refined method and design fabricating parylene neurocages for in vitro studies of live neural networks. This fabrication process is less complex than previous neurocage and neurowell fabrication processes. Parylene neurocages are biocompatible and very robust, making them ideally suited for studying the synaptic connections between individual neurons to gain insight into learning and memory. TThe study showed that biocompatible and robust neurocages can be created that achieve significantly higher neuronal survival and outgrowth rate than previous versions. Previous neurocage designs achieved limited neuronal outgrowth; the long-term cell survival rate was <25%. As outlined here, the incorporation of new materials and different anchoring techniques, in addition to some design modifications, have improved the long-term cell survival rate to >50%.
Keywords: Biocompatible parylene neurocages; Learning; Live neural networks; Long-term cell survival rate; Memory; Neurocage; Neuronal outgrowth; Neuronal survival; Neurons; Neurowell fabrication; Synaptic connections